Design and construction of urban stormwater management systems (American Society of Civil Engineers ; Water Environment Federation, 1992)
This Manual updates relevant portions of the "ASCE/WPCF Manual of Practice No. 37", "Design and Construction of Sanitary and Storm Sewers". This update is necessary due to the many changes taking place in the field, such as the use of microcomputers and the need to control the quality of runoff, as well as the quantity. In order to broaden the base of experience reflected in the Manual, each chapter was prepared by one or more authors with experience and expertise in the particular subject area. Thus, the Manual aids the practicing engineer by presenting a brief summary of currently accepted procedures relating to the following areas: financial services; regulations; surveys and investigations; design concepts and master planning; hydrology and water quality; storm drainage hydraulics; and computer modelling. -- Provided by publisher.
Keywords: Urban runoff -- Management.; Storm sewers -- Design and construction.; elektronické knihy; electronic books